PENGARUH GERAK DAN LAGU TERHADAP KEPERCAYAAN DIRI ANAK USIA 4-5 TAHUN DI TK RAUDHATUR RAHMAH KECAMATAN MARPOYAN DAMAI PEKANBARU - Rubinah Rubinah; Daviq Chairilsyah; Hukmi Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims 1) To determine the child's confidence before the application of movement and song. 2) To determine the child's self confidence after the adoption of the motion and song. 3) To determine how much influence the implementation of the motion and the song of the child's confidence. This type of research used in this research is the experimental approach of a study that sought influence of certain variables on other variables in strictly controlled conditions. In this case that is the subject of this research is in TK Raudhatur Rahmah Marpoyan Damai Pekanbaru with the number of children 12, 5 boys and 7 girls. Collecting data using observation and documentation. Collecting data using observation and documentation. Based on the survey results revealed that 1) the ability of self-confidence of children aged 4-5 years in TK Raudhatur Rahmah Marpoyan Damai Pekanbaru before treatment is given in the form of the motion and the song is low. 2) The ability of the confidence of children aged 4-5 years in TK Raudhatur Rahmah Marpoyan Damai Pekanbaru after treatment is given in the form of motion and tracks have increased and relatively high. 3) Motion and the songs have a significant effect on confidence in the ability of children aged 4-5 years in TK Raudhatur Rahmah Marpoyan Damai Pekanbaru. It can be seen that there are differences in the form of increased confidence in the ability of children before and after treatment. And track motion has the effect of 30.56% confidence in the ability of children aged 4-5 years TK Raudhatur Rahmah Marpoyan Damai Pekanbaru.Keywords: Motion And Songs, Confidence